Clival canal Angle and Basal Angle in Nepalese Population- A Computed Tomography Based Study - Rajbanshi, Jagat Narayan; Chaudhary, Archana; Nepal, Pankaj Raj; Thapa, Dinesh Kumar; Yadav, Navin Kumar (Eastern Green Neurosurgery, 2020)
Background: Clival canal angle is an angle formed by the clivus and the posterior longitudinal ligament of the cervical spine and Welcher basal angle formed between the line joining the nasion to tuberculumSella and the line joining the tuberculum sellae to basion along the plane of clivus. With the aim to review the normal distribution of clival canal angle and basal angle in the Nepalese population this study was performed. Methods and materials: This is a cross-sectional analytical study with non- probability consecutive sampling technique done over the duration of 3 months. A reconstructed image of a bone window in the midsagittal plane was selected and measurement of the angles was done in CT console. Results: There was a total of 60 patients in this study with male predominance (figure 3). The mean age of the population was 49.8 (SD 18.8) years. The clival canal angle reference range was 130.8 to 168.8 degrees with a mean 149.8(SD 9.5) degree. Similarly, the reference range of Welcher basal angle in the study population was 115.49 to 140.29 degree with a mean of 127.89(SD: 6.4) degrees. Conclusion: The mean clival canal angle in the Nepalese population is 149.8 (SD: 9.5) degrees and the mean basal angle is 127.89(SD: 6.4) degree.